Manajemen Sarana dan Prasarana Pendidikan pada SMA Negeri 5 Banda aceh - Mulida, Murniati, Niswanto (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Educational facilities and infrastructure needs a good management. This study aimed to find out the management of educational facilities and infrastructure carried out by principal, the efforts in planning the needs of educational facilities and infrastructure, the utilization and maintenance process carried out by principal in the management of educational facilities and infrastructure. To achieve the aim, this study used qualitative approach. The techniques of data collection were interview, observation, and documentation study. The procedures of data analysis were data reduction, data display, and verification. The subjects of the study were the principal, vice principal, teachers, administrative staffs, and laboratory and library staffs. The results of the study showed that: (1) the process of planning educational facilities and infrastructure included aspect of: (a) provision of educational facilities and infrastructure in order to fulfill the needs in accordance with the development of education each year, (b) provision of educational facilities and infrastructure in order to be able to be conducted in form of displacement from one place to another place, (c) the maintenance of educational facilities and infrastructure was attempted to be always in good condition. (2) The utilization of educational facilities and infrastructure was very effective and able to produce a final goal of education program; and (3) The effort of principal in maintenance process in order to prevent or reduce the damage of facilities and infrastructure was by conducting maintenance to equipment like projector, computer, and laboratory equipment continually, regular maintenance, emergency maintenance, and preventive maintenance in order the facilities and infrastructure would be always effectively function.